Substance use disorder and schizophrenia: prevalence and sociodemographic characteristics in the Latin American population - Jiménez Castro, Lorena (2011)
artículo (preprint) -- Universidad de Costa Rica. Centro de Investigación en Biología Celular y Molecular, 2011